Spectroscopic Analysis of the Extracellular Matrix in Naked Mole-Rat Temporomandibular Joints - Tetsuya Adachi; Hayata Imamura; Toyonari Yaji; Kentaro Mochizuki; Wenliang Zhu; Satoru Shindo; Shunichi Shibata; Keiji Adachi; Toshiro Yamamoto; Fumishige Oseko; Osam Mazda; Kyoko Miura; et al. (Gels, 2025)
Naked mole-rats are extremely long-living rodents with a maximum lifespan of 37 years, and their cellular aging and tissue aging are almost nonexistent. Therefore, in this study, we aim to analyze the extracellular matrix of the temporomandibular joint (TMJ) of naked mole-rats at the molecular level and explore the molecules involved in anti-aging and their localization. Micro-computed tomography (CT) scans revealed increased mineral density and wear of the mandibular condyle in aged mice. Conversely, CT scans did not reveal wear of the mandibular condyle in naked mole-rats, and histological analysis did not reveal wear of the articular disk. Using various spectroscopies and artificial intelligence (AI), we found that the articular disk of naked mole-rats is composed of a cartilage-like layer with hyaluronic acid and collagen fibers with varying orientations, which is thought to have relieved mechanical stress and have protected the mandibular condyle. These results suggest that not only the amount, but also the spatial distribution of the extracellular matrix is important for the anti-aging properties of the TMJ, and may contribute to elucidating the pathology of TMJ disorders and other degenerative conditions and developing therapeutic drugs.